Evaluating LeGaL - An NCL extension for representing Location-Based Games - Ferreira, Cristiane; Salles, Carlos; Santos, Luís; Trinta, Fernando; Viana, Windson (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
A pervasive game extends its experience beyond the virtual world by extrapolating its boundaries to the player’s physical world. One outstanding example of pervasive games is the Location-Based Game (LBG) genre, which takes into account the players’ geographic position in the game rules and mechanics. In this paper, we present an initial evaluation of LEGaL, a language to model and represent the structure and multimedia contents of LBGs. LEGaL allows the modeling of mission-based games by supporting spatial and temporal relationships between game elements. In fact, LEGaL is an extension of NCL (Nested Context Language). We evaluated the proposed language with a group of five NCL developers aiming at investigating if LEGaL is still NCL-friendly. Results indicate LEGal is easily used by this kind of developers.